Facile synthesis of Ni3S2 and Co9S8 double-size nanoparticles decorated on rGO for high-performance supercapacitor electrode materials. (1st February 2017) - Chang, Yuan; Sui, Yanwei; Qi, Jiqiu; Jiang, Liyang.; He, Yezeng; Wei, Fuxiang; Meng, Qingkun; Jin, Yunxue
Highlights: A facile and cost-effective way was developed to produce rGO/Ni3 S2 /Co9 S8 composite. Ni3 S2 and Co9 S8 double-size nanoparticles were decorated on rGO sheets. rGO/Ni3 S2 /Co9 S8 composite electrode presents excellent capacitive performance. Abstract: A facile and cost-effective way has been developed to fabricate a unique structure of Ni3 S2 and Co9 S8 double-size nanoparticles decorated on rGO (coated on the surface of nickel foam (NF)) and the as-prepared rGO/Ni3 S2 /Co9 S8 composite was directly applied as the electrode for a high-performance supercapacitor. In the absence of rGO, Co-doping Ni3 S2 nanoparticles (Co-Ni3 S2 ) were produced. Detailed electrochemical measurements showed that the rGO/Ni3 S2 /Co9 S8 composite electrode exhibited high specific capacitance of 1929.1 F g −1 compared to that of Co-Ni3 S2 electrode of 1075.5 F g −1 at a current density of 1 A g −1 . In addition, the rGO/Ni3 S2 /Co9 S8 composite displayed excellent rate capability (1669.2 F g −1 at 20 A g −1 ) and good cycling ability (92.8% capacitance retention after 1000 cycles at a current density of 10 A g −1 ). The enhanced electrochemical performances of rGO/Ni3 S2 /Co9 S8 composite can be mainly attributed to the positive synergic effect of the unique structure. The facile, low-cost and novel synthesis method and outstanding performance make the rGO/Ni3 S2 /Co9 S8 composite an ideal electrode material for the electrochemical energy storage devices.